Pemeriksaan Kadar Asam Urat sebagai Skrining Hiperurisemia: Strategi Promotif dan Preventif dalam Menekan Risiko Gout - Kosasih, Robert; Santoso, Alexander Halim; Wijaya, Bryan Anna; Andersan, Jonathan; Lo, Geoffrey Christian (Journal of Community Service and Society Empowerment, 2026)
Hyperuricemia is a metabolic health issue that often goes undetected early, despite its strong association with gout and other metabolic diseases. This community service program aimed to improve early detection of hyperuricemia through uric acid screening and to provide promotive and preventive education on risk factors and their management. Conducted at Asisi Church, South Jakarta, the program involved 99 elderly participants and applied a Plan-Do-Check-Action (PDCA) approach. Uric acid levels were measured using point-of-care testing (POCT) with capillary blood, accompanied by education on low-purine diets, physical activity, and adequate hydration. The mean uric acid level was 4.69 mg/dL (SD 1.39), with 9 participants (9.1%) identified as having hyperuricemia. Although most participants were within normal limits, the screening revealed previously undetected cases among older adults with metabolic risks. This activity enhanced health literacy and strengthened the role of community health cadres, demonstrating that community-based POCT screening is feasible for integration into primary care and posbindu programs as a sustainable strategy to prevent gout and metabolic diseases.